Highly sensitive AuNSs@AgNR SERS substrates for rapid determination of aromatic amines. Issue 4 (12th January 2023) - Zhang, Qian; Liu, Zhenglin; Zhang, Hengchang; Han, Caiqin; Wu, Ying; Yan, Changchun; Liu, Ying; Wu, Bin; Yang, Guohai; Duan, Peitong
Abstract : A rapid surface-enhanced Raman scattering (SERS) method based on gold nanostar-modified silver nanorods (AuNSs@AgNRs) was established for the label-free detection of aromatic amines. Abstract : The leakage of aromatic amines will pose a great threat to human health and the ecological environment. Therefore, there is an urgent need to achieve rapid and high-sensitivity detection of such substances. In this study, a simple surface-enhanced Raman scattering (SERS) method based on gold nanostars-modified silver nanorods (AuNSs@AgNRs) was established for the detection of benzidine and 4-aminobiphenyl (4-ABP). The enhancement factors of the substrate towards rhodamine 6G (R6G) and crystal violet (CV) were 4.67 × 10 8 and 1.11 × 10 8, respectively. Combined with density functional theory (DFT), the AuNSs@AgNR substrate achieved the rapid detection of benzidine and 4-ABP and obtained low detection limits (LODbenzidine = 7.09 × 10 −9 M; LOD4-ABP = 1.20 × 10 −9 M). Furthermore, the AuNSs@AgNR substrate can realize the high-sensitivity detection of benzidine and 4-ABP in the spiked river water samples within 3 min, which means that the AuNSs@AgNR-based SERS method can be used as a portable platform to realize the on-site rapid detection of environmental pollutants.